Pine wilt disease and the pinewood nematode: a threat to Mediterranean pine forests. - Mota, Manuel (2012)
Bursaphelenchus xylophilus, the pinewood nematode (PWN), is the causal agent of pine wilt disease (PWD). It was detected for the first time in Europe in 1999, in declining maritime pine (Pinus pinaster) in Portugal. The PWN has been detected in new pine (P. pinaster) forest areas in the center of the country, in 2008, despite efforts developed by the national forestry and quarantine authorities to control the nematode and its insect vector (Monochamus galloprovincialis). The nematode has also recently been reported to be present in Spain, again in P. pinaster. Circulation of non-treated wood and wood products, i.e. human action, is certainly responsible for the worldwide spread of the nematode. The nematode constitutes a threat to the rest of Europe, and namely to Mediterranean pine forests, if proper measures are not taken by European governments. Species such as P. pinaster, P. nigra and in particular P. sylvestris are considered highly susceptible to PWN. In this presentation, some of the strategies currently under way in Portugal to find a solution for the PWN will be discussed. These include, among others, the identification of naturally resistant P.pinaster trees, the identification of quantitative trait loci (QTLs) for PWN resistance, identification of resistance genes using 454 pirosequencing and suppressive subtraction hybridization, and genetic transformation of P. pinaster.